Young adult survivors of childhood acute lymphoblastic leukemia show evidence of chronic inflammation and cellular aging. Issue 21 (27th June 2017) - Ariffin, Hany; Azanan, Mohamad Shafiq; Abd Ghafar, Sayyidatul Syahirah; Oh, Lixian; Lau, Kee Hie; Thirunavakarasu, Tharshanadhevasheri; Sedan, Atiqah; Ibrahim, Kamariah; Chan, Adelyne; Chin, Tong Foh; Liew, Fong Fong; Jeyamogan, Shareni; et al.
Abstract : BACKGROUND: Large epidemiologic studies have reported the premature onset of age‐related conditions, such as ischemic heart disease and diabetes mellitus, in childhood cancer survivors, decades earlier than in their peers. The authors investigated whether young adult survivors of childhood acute lymphoblastic leukemia (ALL) have a biologic phenotype of cellular ageing and chronic inflammation. METHODS: Plasma inflammatory cytokines were measured using a cytometric bead array in 87 asymptomatic young adult survivors of childhood ALL (median age, 25 years; age range, 18‐35 years) who attended annual follow‐up clinic and compared with healthy, age‐matched and sex‐matched controls. Leukocyte telomere length (LTL) was measured using Southern blot analysis. RESULTS: Survivors had significant elevation of plasma interleukin‐2 (IL‐2), IL‐10, IL‐17a, and high‐sensitivity C‐reactive protein levels (all P < .05). A raised high‐sensitivity C‐reactive protein level (>0.8 mg/dL) was related to increased odds of having metabolic syndrome (odds ratio, 7.256; 95% confidence interval, 1.501‐35.074). Survivors also had significantly shorter LTL compared with controls (median, 9866 vs 10, 392 base pairs; P = .021). Compared with published data, LTL in survivors was similar to that in healthy individuals aged 20 years older. Survivors who received cranial irradiation had shorter LTL compared with those who had not ( P = .013). CONCLUSIONS: Asymptomatic young adult survivors of childhood ALL demonstrate a biologic profile of chronic inflammation and telomere attrition, consistent with an early onset of cellular processes that drive accelerated aging. These processes may explain the premature development of age‐related chronic conditions in childhood cancer survivors. Understanding their molecular basis may facilitate targeted interventions to disrupt the accelerated aging process and its long‐term impact on overall health. Cancer 2017;123:4207–4214. © 2017 American Cancer Society . Abstract : Compared with peers of the same age without cancer, young adult survivors of childhood leukemia have evidence of cellular aging that may predispose them to develop debilitating chronic conditions at earlier than expected ages. C‐reactive protein is a robust inflammatory biomarker and has clinical utility in the health surveillance of childhood cancer survivors.